A Bibliometric Approach and Visualization of Waqf Crowdfunding Literature - Taqiyyah, Adzra; Anggraeni, Reni (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
Waqf has significant global potential and can be optimized through innovative approaches, includingthe integration of financial technology (fintech), such as crowdfunding. Waqf crowdfunding is aninnovative approach to collecting waqf funds through a digital platform, which can increase efficiencyand expand the reach of public participation. This study aims to map trends and visualization of waqfcrowdfunding literature in order to provide recommendations for further studies. This study employs adescriptive quantitative approach, utilizing bibliometric analysis of 67 documents sourced fromGoogle Scholar and Scopus, spanning the period from 2016-2024. Data analysis and visualizationwere conducted using VOSViewer, which provides insights into citation patterns, publication trends,and research networks. This study reveals the contributions of 144 researchers, resulting in 67publications that have garnered a total of 895 citations, with the highest annual citation count of 374in 2017. Malaysia and Indonesia show significant roles in the development of waqf crowdfunding,with the most significant contributions of 33 and 30 documents, respectively. This study also identifiesthree main clusters that can be further developed, namely the use of waqf crowdfunding platforms,crowdfunding waqf models (CWM), and waqf crowdfunding case studies. The findings providerecommendations for future researchers to explore several themes related to the main clusters, suchas the use of blockchain technology on waqf crowdfunding platforms, integration of waqf crowdfunding models with other types of waqf such as green waqf or cash waqf linked Sukuk, andcomparative case studies involving multiple platforms or certain countries.